Nitrogen and boron doped carbon layer coated multiwall carbon nanotubes as high performance anode materials for lithium ion batteries - Bo Liu (Nature Portfolio, 2021)
Abstract Lithium ion batteries (LIBs) are at present widely used as energy storage and conversion device in our daily life. However, due to the limited power density, the application of LIBs is still restricted in some areas such as commercial vehicles or heavy-duty trucks. An effective strategy to solve this problem is to increase energy density through the development of battery materials. At the same time, a stable long cycling battery is a great demand of environmental protection and industry. Herein we present our new materials, nitrogen and boron doped carbon layer coated multiwall carbon nanotubes (NBC@MWCNTs), which can be used as anodes for LIBs. The electrochemical results demonstrate that the designed NBC@MWCNTs electrode possesses high stable capacity over an ultra-long cycling lifespan (5000 cycles) and superior rate capability even at very high current density (67.5 A g−1). Such impressive lithium storage properties could be ascribed to the synergistic coupling effect of the distinctive structural features, the reduced diffusion length of lithium ions, more active sites generated by doped atoms for lithium storage, as well as the enhancement of the electrode structural integrity. Taken together, these results indicate that the N, B-doped carbon@MWCNTs materials may have great potential for applications in next-generation high performance rechargeable batteries.